Eksistensi Multi-Party Interim Appeal Arbitration Arrangement Sebagai Arbitrase Pasca Kekosongan Anggota Appellate Body World Trade Organization - Wahyuni, Rani Sri; Jayakusuma, Zulfikar; Diana, Ledy (PATTIMURA Legal Journal, 2024)
Introduction: The World Trade Organization (WTO), as a World Trade Organisation, has a dispute settlement system that allows member countries to comply with the results of the dispute decision through several stages of settlement, namely consultations, panels and the Appellate Body. Since 2017, one of the WTO's member countries, the United States, has not agreed to the appointment of Appellate Body members, resulting in a vacancy in the Appellate Body and its inability to resolve appeals since 2019. To provide a temporary solution to the Appellate Body's dysfunction, several WTO members have established an alternative dispute settlement body, the Multi-Party Interim Appeal Arbitration Arrangement. The establishment of this body is intended to fill the temporary void created by the Appellate Body's dysfunction. Purposes of the Research: The purpose of this study is to determine the existence of the Multi-Party Interim Appeal Arbitration Arrangement in the WTO dispute settlement system. Methods of The Research: The type of research used is normative research by conducting a literature study through data sources derived from legal materials. Results of the Research: The results of this study indicate that the existence of the Multi-Party Interim Appeal Arbitration Arrangement as arbitration after the vacancy of the WTO Appellate Body members does not provide a real solution and instead creates uncertainty among WTO member countries because the Multi-Party Interim Appeal Arbitration Arrangement is not binding and is outside the WTO dispute settlement system. The position of the Multi-Party Interim Appeal Arbitration Arrangement which is outside the system causes a lot of uncertainty and the resulting decisions are not binding.